Global and national university rankings: A multivariate analysis - Т. А. Salimova; I. А. Ivanova; Е. А. Sysoeva (Russian State Vocational Pedagogical University, 2021)
Introduction. In the context of globalisation and internationalisation of higher education, university rankings are becoming an important tool for assessing the quality of education received by students at various higher education institutions around the world. These processes actualise the issues of possibilities for practical use of methodologies for calculation of global and national university rankings.The aim of the study was to develop and apply a methodological approach to multivariate the analysis of Higher Education Institutions (HEIs) classification procedures, to construct and analyse aggregated indicators for global and national rating systems of higher education organisations, and to assess the relationship between them.Methodology and research methods. The current paper presents a system analysis of databases of rating systems and an aggregation of independent evaluations of global and national rankings of HEIs using the methodology of league table analysis based on mathematical apparatus of the voting theory. The dependence of global and national university rankings indicators was investigated using correlation, cluster, factor, regression (linear and polynomial) and dispersion methods of analysis.Results and scientific novelty. A comprehensive comparative analysis of ranking systems and their results was carried out. The authors solved the problem of aggregating multiple heterogeneous studies of global and national ranking systems with their qualitative and quantitative variety of criteria, indicators and methods of assessment. The correlation between the indicators of aggregated global and national rankings was revealed; the regression dependence of the integral national ranking with the results of the leading global rating systems was determined.Practical significance. The developed methodical approach is a convenient and effective mechanism for comprehensive monitoring of the members of educational process.